The research on the attitudes toward disabled people in the educational settings: A scientometric evaluation - Konur, Özcan (SILA SCIENCE, 2013)
The present study explores the characteristics of the literature on the attitudes toward their disabled people published during the last three decades, based on the databases of Science Citation Index-Expanded (SCIE) and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this study reveal that the literature in this field has grown steadily during this period reaching to 655 papers in total with paralleling enormous changes in the research landscape. Papers were mostly journal articles, reviews, and proceedings, and being predominantly in English. The US was the most publishing country producing 54% of the output. The "Bar Ilan University" of Israel was the most contributing institution and the most publishing author was "Livneh H". "Rehabilitation Counseling Bulletin" was the most publishing journal whilst "Rehabilitation" was the most published subject area. The total number of citations was 5,262 resulting in 8.03 average citations per paper and "H-index" of 29. "Donaldson J" [1] had the highest impact on the literature. The results of this first ever such study of its kind showed that the scientometric analysis has a great potential to gain valuable insights into the evolution of the research on the attitudes toward disabled people.
Keywords: SSCI; Scientometrics; Web of Knowledge; SCIE; Attitudes toward disabled people; Incentive structures; Research evaluation; Research productivity